Determinants of Ayo SRC Application Success in Supporting MSMEs Go Digital - Hanifah, Riskah; Restianto, Yanuar (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2025)
ABSTRACTÂ  This survey was conducted on SRC shop owners who use the AYO SRC Application in the Banyumas Regency. This research is entitled: "Determinants of the Success of the AYO SRC Application in Supporting MSMEs Go Digital". The purpose of this study was to determine the effect of system quality, service quality, user intensity, and user satisfaction on system success that provides efforts in supporting Go Digital MSMEs. The population in this study was 1176 SRC stores in Banyumas Regency. The number of respondents taken in this study amounted to 115 respondents. The sampling method used purposive sampling method. Based on the results of research and data analysis using SEM (Structural Equation Modeling) show that: (1) The better the quality of the system, the higher the intensity of system users, (2) The better the quality of the system, the higher the user satisfaction, (3) The high and low quality of service has no effect on user intensity, (4) The better the quality of service, the higher the system user satisfaction, (5) The higher the user satisfaction, the higher the intensity of system use, (6) The higher the user intensity, the greater the system success, (7) User satisfaction has a significant positive effect on system success, (8) The higher the system success, the higher the efforts in supporting MSMEs Go Digital. This study implies that in increasing the intensity of AYO SRC Application users, the Company should continue to develop good service, responsiveness, assurance, and empathy for complaints or problems felt by SRC Stores, and is expected to continue to provide programs that are beneficial to SRC Stores, so that SRC Stores will continue to use and use the AYO SRC Application more often. Further research is recommended to expand the research area nationally so that the number of samples is greater and add variables that are not yet in this study. Â 